An easy method for diagnosing macro-aspartate aminotransferase: A case series - Beşer, Ömer Faruk; Laçinel, Sibel; Gülcü, Didem; Kutlu, Tufan; Çullu Çokuğraş, Fügen; Erkan, Tülay (Turkish Journal of Gastroenterology, 2014)
Abstract Macro-aspartate transaminase (macro-AST) must be considered when the aspartate transaminase (AST) level is chronically high without any liver, cardiac, or muscle disease. Many specialized laboratory techniques have been recommended for diagnosing macro-AST, including the polyethylene glycol immune precipitate technique, which is simple. This study presents a considerably easier method based on the studies of Davidson and Watson and Castiella et al. Our method is based on the decrease in the plasma AST level after storage of the macroenzyme at 2-8°C for 5 days, and has the advantages of low cost, reliability, and practicality at any health center. In our eight cases of macro-AST, the AST activity at day 6 had decreased by more than 50% from day 1. This method is practical for primary healthcare facilities because of its easy application and accurate results, and obviated the need for unnecessary tests after diagnosis.